Exploration of Local Durian (Durio zibethinus Murr.) from Semen Sub- District, Kediri, East Java Based on Morphological Character and Geograpical Factor (Jurnal Online Pertanian Tropik, 2023)
The purpose of this study is to identify morphological characters and determine the local durian distribution map in Semen District, Kediri Regency. This study uses a purposive sampling method to collect data. Local durian coordinates analyzed using QGIS version 3.6 software. Morphological character is examined by observing morphology. Micro climate factors measured are height, intensity, temperature and humidity of the soil and air, soil pH. The results show that local durin morphology in Semen District Kediri Regency has diversity. There are 10 local durian plants found based on their geographical character. The dendogram results show that local durian has similarities based on its morphological character. This morphological  variation  dependent  to  light  intensity,  altitudinal,  the  velocity  of  wind and  soil nutrient factors.